Metal ion recovery from electrodialysis-concentrated plating wastewater via pilot-scale sequential electrowinning/chemical precipitation. (1st January 2022) - Kim, Joohyun; Yoon, Sunho; Choi, Minhee; Min, Kyung Jin; Park, Ki Young; Chon, Kangmin; Bae, Sungjun
Abstract: Metal recovery from industrial wastewater can be achieved by electrowinning (EW) and chemical precipitation (CP), but this is challenging because of the low concentration of metal ions in the wastewater, especially that from metal plating plants, as well as the presence of other organic and anionic species. However, electrodialysis (ED) is a promising method for concentrating the metal species in wastewater. Therefore, in this study, we developed and operated a pilot-scale ED system for the treatment of real plating wastewater, obtaining ED-concentrated plating wastewater in the concentration compartment for the selective recovery of Cu and other metals using pilot-scale EW and CP processes, respectively. The ED process was run at 200 V (13.3 V/cell-pair) and produced plating wastewater having metal concentrations up to two orders of magnitude greater than that of the input wastewater. A cell voltage of 2.0 V was selected for EW because it yielded an appropriate current density and the selective recovery of Cu as Cu(0) and Cu2 O without producing metallic sludge. We obtained almost 93%–96% Cu-selective recovery (initial [Cu] = 790–1145 mg/L) from the ED-concentrated plating wastewater samples via our pilot-scale EW process, which had a specific energy consumption of 3.5–5.3 kWh/kgCu . In the CP process, we found that hydroxide precipitation allowed the selective recovery of amorphous Fe(OH)3 /Fe–Cr complexes at pH 4–5 and β-Ni(OH)2 /λ-Zn(OH)2  at pH values exceeding 7. Thus, the sequential EW/CP system is suitable for the treatment of ED-concentrated plating wastewater and the recovery of valuable metals. Graphical abstract: Image 1 Highlights: Pilot-scale electrodialysis/electrowinning/chemical precipitation was developed in this study. ED-concentrated plating wastewater was used for metal recovery by sequential EW/CP. Ten cycles of ED produced eight-times higher conductivity than initial plating wastewater. Cu-selective recovery by EW had a specific energy consumption of 3.5–5.3 kWh/kgCu . Fe(OH)3 /Fe–Cr complexes and β-Ni(OH)2 /λ-Zn(OH)2 were precipitated in CP process.